Efektivitas Konseling Sebaya untuk Mereduksi Kecanduan Game Online pada Siswa SMP - Rischa Pramudia Trisnani; Silvia Yula Wardani (Indonesian Journal of Educational Counseling, 2020)
THE EFFECTIVENESS OF PEER COUNSELING TO REDUCE ONLINE GAME ADDICTION IN MIDDLE SCHOOL STUDENTS. The ease of using the internet is currently widely used by teenagers to operate online games. Online games are games that can be played together through a network. The high frequency of online game usage results in teens experiencing online game addiction. Friends are people outside the family who can provide comfort for teenagers. Through peer counseling, they hope to be able to exchange ideas and assess which actions are necessary or not to take. The purpose of this study is to test the effectiveness of peer counseling to reduce online game addiction in students. The method used in this research is experimental research. The design of this study was pre-experimental design. The sampling technique in this study used porposive sampling where the sample was selected by students who were addicted to online games. Based on the sig (2-tailed) value of 0,000 which is <0.05, it can be concluded that there is a difference between the pretest and posttest scores or effective peer counseling to reduce online game addiction in students.